IDENTIFIKASI PENYALAHGUNAAN PERUNTUKAN RUANG TERBUKA HIJAU PADA PEMBANGUNAN KAWASAN KULINER DI PLUIT JAKARTA UTARA - Almira Muthi Faliha; Annisa Aulia Suwandi; Dewi M Z S Pertiwi; Dedi Hantono (Jurnal Potensi, 2021)
The increasing demand for space, especially for settlements and built-up land, has an impact on the declining environmental quality of the area. The Spatial Plan that has been made is not able to prevent land conversion in urban areas so that the existence of Green Open Space (RTH) is increasingly threatened and the city is increasingly uncomfortable for activities, especially for joint activities. This study will discuss the "Identification of the Use of Green Open Land for the Development of Culinary Areas in Pluit, North Jakarta". The purpose of this study is to determine the availability of green open space in North Jakarta, as well as to find out the existence of matters concerning the misuse of green open space in Pluit, North Jakarta based on local regulations governing Green Open Space. The method used in this analysis is a qualitative descriptive method with data collection techniques in the form of secondary data. Based on the results of the study, it can be seen that the availability of green open land in North Jakarta is only about 5% of the total area, this percentage is still far from meeting the provisions of the law which stipulates that the proportion of green open space in urban areas must reach 30%. The development of the culinary area in Pluit has several violations such as Law Number 26 of 2007 concerning Spatial Planning, which only provides 11% open space, Regional Regulation no. 8 of 2007 concerning Public Order in DKI Jakarta in article 36, because it builds a culinary area adjacent to the High Voltage Air Line (SUTET) and there are buildings that stand on Green Open Land.